Narrative analysis of documentary films by Kanat Beisekeyev as an example of new media publicism (Herald of Journalism, 2022)
The article is devoted to the topic of the search for ethnic identity of Kazakhs in the journalism of new media on the example of the works of Kazakhstani independent director Kanat Beisekeyev. The purpose of the study is to determine the methods of disclosure of this topic through narrative analysis. The research devoted to the study of the YouTube platform as a media for broadcasting documentaries, since the object of the study was published on the personal YouTube channel of director Beisekeyev.This study is an example of the use of narrative analysis of a documentary film as an example of journalism in new media, which represents the scientific value of the work. The author of the article reveals the director's stylistic devices, thanks to which the theme of ethnic identity is revealed more effectively. In terms of practical significance, the article defines a documentary as one of the way to comprehend socially important topics in journalism.The results of the study showed the positive nature of the collaboration between the official media and an independent author based on the YouTube platform. The popularity of video hosting, which has turned into social media in recent years, will grow every year, and therefore it is worth paying attention to the analysis of high-quality, educational content on YouTube. In practical terms, the study makes a proposal to consider the possibility of developing intercultural and interethnic communication through the creation of documentaries.The main message of Beisekeyev's films about the search for the ethnic identity of the Kazakhs is the development of the Kazakh language and preservation of the Kazakh culture.Keywords:  YouTube, documentary, narrative, publicism, new media.